2022
DOI: 10.1099/acmi.0.000485.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of ADC-5 Cephalosporinase in environmental Acinetobacter baumannii from a German tank milk with a novel Sequence Type

Abstract: Bacteria resistant to antibiotics arguably pose the greatest threat to human health in the 21 st century. One such bacterium that typifies antibiotic resistance is Acinetobacter baumannii. Frequently, hospital strains of A. baumannii display multidrug resistant (MDR) or extreme drug resistant (XDR) phenotypes, often requiring the use of last resort antibiotics for treatment. In addition to hospital settings, A. baumannii has been isolated from many highly divergent sources including wastewater treatment plant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Expression analysis was performed according to Sykes et al (12). In brief, overnight cultures of each strain were subcultured 1/100 in LB broth with shaking at 37ºC until mid exponential phase was not certified by peer review) is the author/funder.…”
Section: Rnd Efflux Expression Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression analysis was performed according to Sykes et al (12). In brief, overnight cultures of each strain were subcultured 1/100 in LB broth with shaking at 37ºC until mid exponential phase was not certified by peer review) is the author/funder.…”
Section: Rnd Efflux Expression Evaluationmentioning
confidence: 99%
“…In short, a One Health approach is required (11). By exploring the diversity of non-human Acinetobacter spp., further insight can be gathered into their evolution including novel STs, and antibiotic resistance genes, (12) as well as their potential to cause serious consequences for human health (13). In fact, emerging Acinetobacter spp, such as A. junii (14) and A. berenziniae (15) are being classified as One was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, using several molecular typing strategies (MLST and the gene bla OXA-51 ), found this bacterium in water, milk, meat, cheese and animal samples [7]. A very recent study even found A. baumannii in a milk tank [11]. Clearly, isolates of this pathogen have been found in different types of environments [4,6,7,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study even found A. baumannii in a milk tank [11]. Clearly, isolates of this pathogen have been found in different types of environments [4, 6, 7, 9, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Tracking of clonal spread also aids in tracking ARGs and VGs associated with particularly concerning clones. However, more and more often, A. baumannii from non-clinical sources (10)(11)(12)(13) are being interrogated because they too harbour ARGs and VGs. In fact, A. baumannii has been classified as a One Health problem (14), which encompasses all aspects of human, animal and environmental health.…”
Section: Introductionmentioning
confidence: 99%